2002
DOI: 10.1149/1.1463400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Nonstoichiometry on a La[sub 1−x]A[sub x]MnO[sub 3+δ] Cathode under a Polarized State

Abstract: Lanthanum manganite, the air electrode material of solid oxide fuel cells, is well known for its complicated nonstoichiometry, which depends upon oxygen partial pressure and temperature. This nonstoichiometry has a relationship with electrode reactivity or the exchange current density because it affects the oxygen activation step. The electrode reactivity is usually studied in terms of its exchange current density, in other words, under a nonpolarized ͑equilibrium͒ state. This paper aims to elucidate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…99 Under the condition that the nonstoichiometry variation in La 1¹x Sr x MnO 3+D is negligibly small, we find that Q E is proportional to P(O 2 ) 1/2 . 22,44,45,66,70 With the increase in oxygen content, Q E becomes smaller than the value expected from the P(O 2 ) 1/2 relationship. 44,45,66 Similarly, ac impedance measurements under polarization revealed that Q E varies with not only the gas phase P(O 2 ) but also by the electrode potential determined by the chemical overpotential defined by Eq.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…99 Under the condition that the nonstoichiometry variation in La 1¹x Sr x MnO 3+D is negligibly small, we find that Q E is proportional to P(O 2 ) 1/2 . 22,44,45,66,70 With the increase in oxygen content, Q E becomes smaller than the value expected from the P(O 2 ) 1/2 relationship. 44,45,66 Similarly, ac impedance measurements under polarization revealed that Q E varies with not only the gas phase P(O 2 ) but also by the electrode potential determined by the chemical overpotential defined by Eq.…”
mentioning
confidence: 83%
“…(11). 45,70 The lattice parameter decreases with the increase in oxygen content, irrespective of defect species. 100,101 It is considered that the lattice parameter decrease is related to the decrease in the surface diffusivity of O ad .…”
mentioning
confidence: 98%
“…This finding was later confirmed by Hansen et al [4] at a somewhat lower temperature of 500 °C. In contrast, Yasamoto et al [5] found that the activity of LSM10 was much higher than the activity of LSM40, using porous planer electrodes. In a later publication, Hansen [6] showed that at temperatures of 400 °C or less, a less clear dependence on the composition existed.…”
Section: Introductionmentioning
confidence: 84%
“…These results suggest that higher electrochemical activity of cathode materials becomes essential with decreasing operating temperature. Following empirical equation related to the cathode reaction was obtained by the fitting procedure: [4] Anodic Exchange Current Density vs. Operating Conditions…”
Section: Cathodic Exchange Current Density Vs Operating Conditionsmentioning
confidence: 99%
“…Concerning the cathode reactions, the values of __ and ___ have been reported in the literature (1)(2)(3)(4)(5). These values are summarized in Table II.…”
Section: Mechanism Of Cathode Reactionsmentioning
confidence: 99%